The theory of political culture - Welch, Stephen (Oxford Oxford University Press, 2013)
Developing a theory of political culture as consisting of two dimensions, discourse and practice, the book explains how political culture can both inhibit political change and be a source of it. It explores the nature and dynamics of political culture systematically and comprehensively, and suggests numerous new lines of empirical research.
Includes bibliographical references and index.
Keywords: Political culture